Withdrawal holding strength analysis of tapered threaded metal inserts in medium density fibreboard (MDF) / Kamarulzaman Nordin …[et al.] - Nordin, Kamarulzaman; Jamaludin, Mohd Ariff; Ahmad, Mansur; Alias, Asmalila (2006)
The withdrawal holding strength of two sizes of tapered threaded metal insert fastener i.e. 4mm diameter by 10mm length (4 X 10) and 6mm diameter by 13mm length (6 X 13) embedded in the face of a commercially manufactured medium density fiberboard (MDF) of 16mm and 19 mm thickness from Malaysia was carried out in this study. The results generally indicated that longer metal inserts with greater depth of embedment produced significantly higher withdrawal holding strengths while diameter of the metal inserts have no significant effect on the holding strength. Further test carried out to determine the effect of pilot holes size on the holding strength indicated that to some extent, the use of optimum pilot holes apparently increases the withdrawal holding strength of threaded metal inserts fastener. However, it should be cautioned that the optimum pilot hole sizes recommended in this study should only be used as first estimates and adjustments should be made as needed for the specific board properties in question.